1967
DOI: 10.1111/j.1476-5381.1967.tb01948.x
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Study of Drug Elimination: The Excretion of Paracetamol and Its Metabolites in Manmetabolites in Man

Abstract: In the preceding paper (Cummings, Martin & Park, 1967) theoretical considerations have been presented relating to a drug which is eliminated by apparent first order processes of urinary excretion and metabolism. These considerations have indicated that when the excretion rate constants of drug metabolites are greater than the elimination rate constant of the drug, plots of log rate of excretion of drug and of drug metabolite eventually become linear and parallel to each other. Experimental verification of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

1967
1967
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(63 citation statements)
references
References 7 publications
1
62
0
Order By: Relevance
“…Acetaminophen is one of the most widely used nonprescription medicines in the world and its toxicology and metabolism have been extensively investigated over many years (14)(15)(16)(17)(18)(19)(20). However, we will show here that, even for this most familiar drug, pharmacometabonomic analysis will yield significantly increased understanding of its metabolic behavior in humans.…”
mentioning
confidence: 99%
“…Acetaminophen is one of the most widely used nonprescription medicines in the world and its toxicology and metabolism have been extensively investigated over many years (14)(15)(16)(17)(18)(19)(20). However, we will show here that, even for this most familiar drug, pharmacometabonomic analysis will yield significantly increased understanding of its metabolic behavior in humans.…”
mentioning
confidence: 99%
“…The dye is absorbed from the blood into the liver so rapidly that the rate of uptake may be neglected in formulating the model. This approach is analogous to the pharmacokinetic practice of neglecting a rapid absorptive process in the determination of elimination rate constants after oral administration of drug (Cummings, King & Martin, 1967 The rate constant (k1) for the removal of the first methyl group from methyl orange was generally somewhat less than that for the second methyl group (I2). Taking into account the higher error of k2, and the fact that in group 3 (Table 3), k2 was actually a little less than ki, it may be concluded that there is not a large difference in the two rate constants.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have considered systems in which drug metabolism is represented as a single first-order process, for example, the acetylation of sulphonamides (Nelson & O'Reilly, 1960;Yamazaki, Aoki & Kamada, 1968). Somewhat more complex systems, in which several metabolites are produced by parallel first-order processes, have been studied by Cummings, King & Martin (1967) with paracetamol, and by Nogami, Hasegawa, Hanano & Imaoka (1968) with sulphonamides. The most common biochemical path for drug metabolism involves two successive reactions: first, metabolical alteration, and then conjugation of-the metabolite (Williams, 1959).…”
Section: Introductionmentioning
confidence: 99%
“…Only 4% of ingested paracetamol is excreted unchanged in the urine. 8 In patients who develop liver damage, however, metabolism is delayed.5 The hepatic toxicity seems to occur rapidly after absorption of the drug and the slow metabolism is thought to be the result rather than the cause of the liver damage. Perhaps for this reason earlier treatments (including corticosteroids and antihistamines,9 heparin,'0 haemodialysis," and charcoalcolumn haemoperfusion12) all failed to prevent liver damage in severely poisoned patients.…”
Section: Treatment Of Acute Paracetamol Poisoningmentioning
confidence: 99%